Potential Antihyperlipidemia Effect of Lactoferrin in Hyperlipidemia-Induced Male Sprague–Dawley Rats - Jusni, Louis Fabio Jonathan; Chandra, Valencia; Djuartina, Tena; Notario, Dion; Arieselia, Zita; Hananta, Linawati (Makara Journal of Health Research, 2022)
Background: Hyperlipidemia is a condition that is characterized as an increase in total cholesterol and triglyceride levels in the blood. Lactoferrin is a protein that can serve as an antioxidant. This study aims to determine whether lactoferrin can reduce total cholesterol and triglyceride levels. Methods: This study used 24 Sprague–Dawley rat strains, which were divided into six groups: normal group; negative control; positive control; and dose groups 1, 2, and 3. The normal group was given standard feed, whereas the other group was given high cholesterol and fat. The positive control group and dose groups 1, 2, and 3 were given 1.5 mg/kg BW of simvastatin and 100, 200, and 400 mg/kg of BW lactoferrin, respectively. After 6 weeks, total cholesterol and triglyceride levels were measured. Results: This study showed that lactoferrin doses of 100, 200, and 400 mg/kg BW could significantly reduce total cholesterol and triglyceride levels (p < 0.05). Lactoferrin could also significantly reduce activated Kupffer cell and steatosis area in the liver (p < 0.05). Conclusions: Lactoferrin can reduce total cholesterol and triglyceride levels. Thus, further research is needed to address the existing bias and confirm that lactoferrin can reduce cholesterol and triglyceride levels.